Incitement to terrorism - Bayefsky, Anne F.; Blank, Laurie R. (Nijhoff law specials, 2018)
Freedom of Expression, Hate Speech, and Incitement to Terrorism and Genocide : Resonances and Tensions -- Public International Law and Cyber Incitements to Violence -- Incitement to Terror and Freedom of Speech -- Wrestling with Freedom of Expression and the Spread of Extremism : A UK Perspective -- French Law and EU Rules in the Fight against Incitement to Terrorism or Violent Extremism -- Canadian Legal Perspectives on Incitement to Terrorism -- Containing the Proliferation of Incitement : A Canadian Perspective -- Incitement and Related Matters in Israeli Law -- Fighting Incitement : The Work and Practice of the Israeli Prosecution 2014-2016 -- The UN and Incitement -- Targeting Speech in War -- Criminal and Military Incitement Response Tools : Prosecution and Security Detention -- Imminence Reconsidered -- Inciting Terrorism on the Internet : The Limits of Tolerating Intolerance -- Combating Incitement to Violence on the Internet through Service Provider Action -- Police and Incitement to Terrorism : The Challenge of Countering Violent Narratives